A standardised in vivo and in vitro test method for evaluating tick repellents - Kröber, Thomas; Bourquin, Martine; Guerin, Patrick (My University, 2013)
The threat of transmission of Lyme borelliosis and tick-borne encephalitis by ixodid ticks has resulted in an increasing number of tick repellents coming onto the market. To allow proper evaluation of the efficacy of different types of compounds and their formulations, there is a need for standardised methods for testing ticks repellents. Ticks show a marked negative geotactic response following contact with a potential host, i.e., they climb up in order to locate attachment and feeding sites, whereas exposing ticks to repellents induces positive geotaxis, i.e., ticks walk downwards or drop off the treated host or substrate. We describe here complementary tests that employ these geotactic responses to evaluate repellents: one in vitro on a warm glass plate and the other on the lower human leg (shin). The compounds tested were DEET, EBAAP, icaridin, capric acid, lauric acid, geraniol, citriodiol, citronella essential oil and lavender essential oil, all non-proprietary ingredients of widely distributed tick repellent formulations.
In controls on both the warm glass plate and the human leg, the majority of Ixodes ricinus nymphs walk upwards. By contrast, in both the in vitro and in vivo tests, effective doses of repellents cause ticks to either walk downwards or fall off the substrates, termed here “affected ticks”. The ED75 values for affected ticks on the human leg indicate that the test products can be divided into three groups: (1) icaridin, EBAAP, DEET and capric acid with values between 0.013 and 0.020 mg/cm2, (2) citriodiol and lauric acid with values between 0.035 and 0.058 mg/cm2, and (3) geraniol, citronella oil and lavender essential oil with values between 0.131 and 1.58 mg/cm2. The latter three products can be considered as less effective repellents. The tests on the warm glass plate resulted in very similar efficacy rankings for the products tested in vivo, and the ticks’ behavioural responses also corresponded closely to those observed on the treated human leg. The ED75 values on the glass plate ranged from half to one sixth needed on the leg. The warm glass plate test thus provides a reliable alternative to human subjects for an initial evaluation of new repellents, and is particularly appropriate for testing products with still to be determined human toxicity and dermatological effects.
Keywords: Tick; Ixodes ricinus; Repellent; Tick behaviour; Repellent test; Geotaxis